INFLUENCE OF LOW-LEVEL LASER APPLICATION ON ROOT RESORPTION AND PULP ALTERATIONS DURING TOOTH MOVEMENT - Marquezan, Mariana; Nunes, Lívia Kelly Ferraz; Freitas, Amanda Osório Ayres; Narciso, Marcelo Sampaio; Nojima, Matilde da Cunha Gonçalves; Araújo, Mônica Tirre de Souza; Bolognese, Ana Maria; Ruellas, Antônio Carlos de Oliveira (Saúde (Santa Maria), 2013)
http://dx.doi.org/10.5902/223658345042 The purpose of this study was to determine the effects of low-level laser (LLL) irradiation on root resorption and dental pulp during experimental tooth movement. Five groups were delineated: a control group without orthodontic force or LLL application, 2 other controls in which orthodontic force was applied for 2 and 7 days respectively, and two experimental groups with orthodontic force and LLL application for 2 and 7 days respectively. To induce experimental tooth movement in rats, orthodontic force of 40 cN was applied to the left first molars. In irradiated groups, Ga-Al-As diode laser (830 nm) was applied on 3 areas around the experimental maxillary molar: mesial, buccal and palatal. Two microscopic analyses were performed with HE staining: a quantitative for root resorption and a qualitative for pulp tissue reactions. Quantitative analysis showed that root resorptions were evident on day 7 of tooth movement. The irradiated group presented twice the amount of root resorption than the orthodontic control group, but this difference was not verified statistically (P=0.073). The qualitative pulp evaluation showed no significant alterations when orthodontic force or LLL were applied. Root resorption was verified when LLL was applied and no undesired effects on pulp tissue were observed. KEY WORDS: laser therapy, low-level; tooth movement; root resorption; dental pulp